Foldable and water-resist electrodes based on carbon nanotubes/methyl cellulose hybrid conducting papers. (1st March 2019) - Ko, Jae Ok; Kim, Seong Ku; Lim, Yi Rang; Han, Jin Kyu; Yoon, Yeoheung; Ji, Seulgi; Lee, Minhe; Kim, Sang-Woo; Song, Wooseok; Myung, Sung; Lim, Jongsun; Lee, Sun Sook; et al.
Abstract: We developed a paper-type electrode for the next-generation wearable devices by complementary hybridization of methyl cellulose and carbon nanotubes (CNTs). The large-scale hybrid paper was fabricated using an incomparably simple and low-cost solution process. Structural features, surface hydrophobicity, and chemical interaction between CNTs and cellulose of the hybrid papers were systematically explored by adjusting the concentration of CNTs. The hybrid papers demonstrated superb mechanical durability even under highly strained conditions such as folding, crumpling and re-flattening regardless of the concentration of CNTs. The electrical properties of the CNTs/methyl cellulose were well-preserved even when folded as origami or submerged in water.